Readiness of micro, small, and medium enterprises (MSMEs) in the food and beverage sector for halal certification implementation: A case study in Magelang, Indonesia - Tuhuteru, Akbar Dwikiwibowo; Iqbal, Muhammad (Universitas Islam Indonesia, 2024)
IntroductionHalal certification is increasingly critical for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially in the food and beverage sector. Despite its mandatory status under Halal Product Assurance Law, many MSMEs face challenges in achieving compliance due to limited knowledge, inadequate service support, and operational constraints.ObjectivesThis study investigates the readiness of MSMEs in Magelang to implement halal certification. It analyzes the influence of knowledge, service quality, halal awareness, production processes, and human resource capabilities on MSME readiness while identifying the most significant factors affecting compliance.MethodThe research employs a quantitative cross-sectional approach, surveying 110 MSME operators in Magelang. Data were collected using structured questionnaires and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis.ResultsThe findings reveal that knowledge, service quality, and halal awareness significantly influence MSME readiness for halal certification, with knowledge being the most dominant factor. Human resource capabilities also positively impact readiness, while production processes were found to be insignificant. The model explains 74% of the variance in readiness, emphasizing the importance of integrating these factors.ImplicationsThe study highlights the need for targeted educational initiatives, streamlined certification processes, and enhanced institutional support to improve MSME compliance. It provides actionable insights for policymakers, certification bodies, and MSME operators to foster a robust halal certification ecosystem.Originality/NoveltyThis research contributes to the understanding of halal certification readiness by offering a multidimensional analysis of critical factors, addressing gaps in existing literature, and proposing practical interventions to enhance MSME participation in the halal market.